The Relationship Between Revelation and Reason in Islam: An Integrative Framework for Knowledge Construction and Worldview Formation - Laila Zaqiyah; Hamdan Hasibuan; Muzanah; Salim Haji; Mustakim; Muhammad Fahrul; Nasywa Nidaul Azmi (Universitas Darunnajah Jakarta, Indonesia, 2026)
This study examines the integrative relationship between revelation (wahy) and reason (‘aql) in Islamic epistemology, with particular emphasis on how their synthesis constructs a coherent worldview and influences Muslim intellectual, social, economic, and spiritual life. Employing a qualitative content analysis approach grounded in library research methodology, this study systematically analyzed primary Islamic sources, the Qur’an and Hadith, alongside classical and contemporary scholarly literature, including works by Ibn Rushd, Ibn Taymiyyah, al-Ghazali, and al-Attas. Thematic analysis was conducted through a three-stage coding process involving open coding, axial coding, and selective coding to identify recurring patterns in the discourse on revelation-reason integration. The findings reveal four principal themes: (1) the epistemological complementarity of revelation and reason as articulated in classical Islamic philosophy; (2) conceptual models of knowledge integration that bridge divine guidance with rational inquiry; (3) persistent challenges in operationalizing this integration within contemporary educational and institutional contexts; and (4) the multidimensional impact of this integration on social cohesion, economic ethics, and spiritual consciousness. This study contributes to the existing literature by proposing a systematic integrative framework that positions revelation and reason not as competing epistemic authorities but as synergistic sources of knowledge essential for addressing contemporary challenges of secularism, materialism, and moral fragmentation.